Composition and structure of grassland vegetation in areas of north and south orientation in the Botanical Garden of Porto Alegre, RS, Brazil - Rolim, Rosângela Gonçalves (2014)
Two areas of native grasslands of Pampa biome with different sun exposures (north and south), and in different periods of mowing exclusion were compared regarding composition and vegetation structure through a phytosociological survey in the Porto Alegre Botanical Garden, Rio Grande do Sul State, Brazil. Sampling was conducted during the spring of 2012 through the distribution of 20 parcels of 1 x 1 m. We recorded 109 species, with 91 species found in the northern area (48 exclusive), and 62 species in the southern area (19 exclusive). Poaceaeobtained the highest importance value in the physiognomy and structure of the vegetation, composed by dominant tussock species ranging in association with rosulate species (northern area) and rhizomatous-stoloniferous species (southern area) of other families. The Shannon index was 3.64 for the general survey, ranging from 4.33 to 3.19 for the northern and the southern areas respectively.